Minutes of the Executive Committee Meetings - Siegfried, John J (American Economic Review, 2001)
Rosen, Stokey, and Taylor as new members of the Executive Committee. He then asked for approval of the minutes of the previous meeting (January 6, 2000) which had been circulated previously. The Secretary reported that he had received a complaint from a member that the minutes did not provide a sufficiently complete account of what is happening. Siegfried took the opportunity to review the customary style of the minutes of the Executive Committee. The minutes do not record who makes and seconds motions nor who speaks in favor or against them; they do summarize the issues raised and the arguments for and against motions. The minutes do not record vote counts, nor who votes for or against a motion; they record whether the motion passes or fails. The minutes do not record precise times individuals enter or leave the room, but rather record who was in attendance for all (or mostly all) of the meeting and who was there for only part of the meeting. Only the final decisions of the Electoral College are recorded in the minutes. After a discussion of the advantages and disadvantages of more detailed minutes, the Executive